2022
DOI: 10.12927/hcq.2022.26980
|View full text |Cite
|
Sign up to set email alerts
|

Improving Family Presence in Long-Term Care during the COVID-19 Pandemic

Abstract: Family caregivers play a vital role in supporting the physical and mental health of long-term care (LTC) residents. Due to LTC visitor restrictions during the COVID-19 pandemic, residents (as well as family caregivers) showed significant adverse health outcomes due to a lack of family presence. To respond to these outcomes, eight implementation science teams led research projects in conjunction with Canadian LTC homes to promote the implementation of interventions to improve family presence. Overall, technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…With protective measures in place, like other non-profit organizations, brain injury associations across Canada started to offer support services online, which increased outreach to clients but also highlighted disparities related to technological accessibility. 29,30 Our findings showed that some clients living with brain injury have difficulty accessing the online programming available at the onset of the pandemic. Brain injury associations worked to reduce the digital divide among individuals with disabilities by providing their clients with devices and teaching materials, as well as financial support to buy devices or pay for internet plans.…”
Section: Discussionmentioning
confidence: 79%
“…With protective measures in place, like other non-profit organizations, brain injury associations across Canada started to offer support services online, which increased outreach to clients but also highlighted disparities related to technological accessibility. 29,30 Our findings showed that some clients living with brain injury have difficulty accessing the online programming available at the onset of the pandemic. Brain injury associations worked to reduce the digital divide among individuals with disabilities by providing their clients with devices and teaching materials, as well as financial support to buy devices or pay for internet plans.…”
Section: Discussionmentioning
confidence: 79%
“…Of the 2530 retrieved studies, 193 were ultimately included 6,7,11–201 . The PRISMA-ScR diagram (Figure 1) shows the study selection process and reasons for full-text exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…To address this issue, eight scientific implementation teams conducted research projects in collaboration with Canadian LTC households, with the aim of promoting interventions to increase family presence 32 . The study found that technological and virtual innovations were effective strategies to promote a stronger family presence in LTC 32 . For Saad et al, 31 86.6% of participants perceived remote visits as a viable strategy.…”
Section: Discussionmentioning
confidence: 99%